How Arabidopsis Receptor-Like Kinase 7 (RLK7) Manifests: Delineating Its Structure and Function - Ramen Chowdhury; M. H. M. Mubassir (Advances in Agriculture)
Like animals, plants customarily utilize cell surface-localized receptors to keep track of environmental stimuli, specifically by plasma membrane-associated receptor-like kinases (RLKs). In comparison to other organisms, plants own a variety of RLKs, which insinuates that ligand-receptor-facilitated molecular mechanisms regulate an array of processes during plant development. Here, we take up Arabidopsis receptor-like kinase 7 (RLK7), which shares the archetypal structure of transmembrane receptor kinases accompanied by a receptor-like ectodomain comprising of leucine-rich repeats (LRRs) along with a functional intracellular kinase domain. Interestingly, this distinctive receptor-like kinase not only orchestrates crucial steps during plant development, including the regulation of seed longevity, dormancy, and seed germination speed, but also plays a role in oxidative stress tolerance, salt stress tolerance, and pattern-triggered immunity. This review deciphers the sequence and structure and evaluates existing knowledge of the function and expression pattern of RLK7.